Environmental factors and satisfaction in a specialty store - Marques, S. (2015)
Given the intense competition experienced in the sector, retailers have been designing strategies to create an environment conducive to consumer satisfaction and purchase, particularly in supermarkets and hypermarkets. This paper develops a conceptualization of customer satisfaction based on field data collected in a specialty store, focusing on the relative importance of the environmental factors on satisfaction. The results show that the most important environmental determinant of customer satisfaction is the variety of products. The help from employees, lighting, layout and design also stand out from the set of stimuli considered.